Implementasi PowToon sebagai Media Pembelajaran Menyimpulkan Teks Diskusi SMP Kelas IX - Wahyu Rahmawati; Asep Yudi Utomo; Fasha Nabilah Aprilliani; Malikhah Malikhah; Iwan Hardi Saputro; Chitra Sintarani; Khlara Martina Sagana (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this study is to determine the effectiveness of the implementation of PowToon media in learning to conclude the discussion text of Junior High School Class IX. This study uses a qualitative descriptive research method to describe the use of PowToon media in the classroom based on observations and interviews conducted. The results obtained from this study are that PowToon media is effectively used for learning to conclude discussion texts because the media can attract students' interest so that students are not bored during learning. In addition, PowToon media can make it easier for teachers to convey various materials that cannot be conveyed only by the lecture method. Based on this, it can be said that PowToon's learning media can be used as a learning medium to conclude discussion texts as a support for the learning process.